Slovenci in problem meja med drugo svetovno vojno - Godeša, Bojan (Acta Histriae, 2015)
The article discusses the problem of the unifi cation of the Slovene ethnic territory through the realization of the national program United Slovenia (the program was al- ready created in 1848) during the Second World War. Before the Second World War, Slo- venes lived in four diff erent states, in Yugoslavia, Italy, Austria (Germany), and Hungary. But their full development was possible only in Yugoslavia, which they considered as their national state, whereas in other three states they had been exposed to assimilation. In April 1941, the Axis forces invaded Yugoslavia and occupied also the Yugoslav part of the Slovene ethnic territory. The three occupying forces (Germany, Hungary, and Italy) tried to eradicate Slovene national identity; the victory and the establishment of the Nazi regime would have meant the ethnocide of the Slovene nation. After the initial shock, the Slovenes put all their hopes in the victory of the Allied Forces. Due to the fact that all neighboring states were in the anti-Allied camp, Slovenes counted on the possibility of realization of United Slovenia. At fi rst, they were quite optimistic, and formed large- scaled territorial demands. The interaction with the international factors on both warring sides made it clear to both opposite Slovene political camps that the realization of United Slovenia would be diffi cult to achieve due to the state of the international political situ- ation in the region. Considering the outcome of the inner-political confl ict, the struggle for the post-war borders became exclusive domain of the resistance movement led by the Communist Party of Slovenia. This struggled resulted in the post-war annexation of a big part of the Slovene Littoral (Primorska) to Yugoslavia. Compared to the First World War, when multiple national states were established on the ruins of the dissolved empires, the Second World War in Europe did not result in radical changes of the socio-political car- tography. The borders changed only in two instances compared to the Versailles Europe % the territorial gains of the Soviet Union, and the annexation of the Slovene Littoral to Yugoslavia. In the context of the wartime and post-wartime development in Europe, the border changes to the Yugoslav western border should be understood as a big exception.
Keywords: svetovna vojna 1939-1945; meje; domoljubje; odporniško gibanje; okupacija; United Slovenia; Zedinjena Slovenija